A HOPS Protein, MoVps41, Is Crucially Important for Vacuolar Morphogenesis, Vegetative Growth, Reproduction and Virulence in Magnaporthe oryzae - Zhang, Xiaojie; Wang, Guanghui; Yang, Chengdong; Huang, Jun; Chen, Xiaofeng; Zhou, Jie; Li, Guangpu; Norvienyeku, Justice; Wang, Zonghua (Frontiers in Plant Science, 2017)
Abstract The homotypic fusion and protein sorting protein complex (HOPS) plays a key role in promoting homotypic vacuolar fusion, vacuolar biogenesis and endocytic trafficking in eukaryotes ranging from fungi to plants and animals. However, its physiological function in the economically destructive rice blast fungus M. oryzae has not been investigated. In this study, we have identified M. oryzae vacuolar protein sorting 41 (MoVps41), an accessory subunit of the HOPS complex, and generated MoVps41 knockout mutants to characterize its function in the growth, reproduction and infectious cycle of the rice blast fungus. Our data showed that MoVps41 is required for the vegetative growth of M. oryzae and depletion of MoVPS41 can abrogate the growth. Furthermore, MoVps41 deficiency can cause vacuolar fragmentation, compromised membrane integrity and reduced pathogenesis in the ΔMovps41 mutant. Our data also provide the first evidence that MoVps41 plays an essential role in the regulation of sexual and asexual reproduction of M. oryzae. In summary, our study provides insight into how MoVps41-mediated vacuolar fusion and biogenesis can have an impact on reproduction, pathogenesis, and vacuolar integrity in M. oryzae, and also underscores the need to investigate the whole HOPS complex in rice blast pathogen.